An Exploratory Study on American- Born Imams: Negotiating Pastoral Responsibilities and Expectations - Askar, Anas (Qualitative Sociology Review, 2021)
Symbolic interactionism, applied in the context of Muslim clerics, suggests that society is constructed based on lived experiences and shared symbolic meanings where people see themselves and the social environment through the eyes of others. For this study, data collected from in-depth interviews were examined to investigate the viewpoints and occupational pathways of American born imams. Thus, this study explored the responsibilities assigned to imams and their communal objectives. Overall, this study found several challenges that imams experienced, professional and organizational. Utilizing symbolic interactionism, these issues were explicated, and the following overarching themes were generated: imams received inadequate training as religious leaders in their communities, relationships between the mosque board and an imam can directly reinforce or mitigate a challenging work environment, and it is most advantageous for American communities to hire American-born imams over foreign-born imams. The findings indicate that organizational support extended to imams from mosque boards leads to not only an amicable relationship but more productive community engagement.